2009
DOI: 10.1136/thx.2008.103671
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between improved airflow limitation and changes in airway calibre induced by inhaled anticholinergic agents in COPD

Abstract: Background: Although airflow limitation improved by inhaled anticholinergic drugs varies among individuals with chronic obstructive pulmonary disease (COPD), the relationship between actual bronchodilation and improved pulmonary function and where in the lung such bronchodilation occurs remains unknown. A study was undertaken to determine the relationship between improved pulmonary function and changes in airway calibre at various sites in the airways in response to inhaled anticholinergic agents in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
2
48
0
1
Order By: Relevance
“…[10][11][12][13] Using data from the COPDGene Study, we observed that emphysema mitigates the increasing effect of WA% on FEV 1 % predicted in subsegmental compared with segmental airways. CT scan measures of emphysema and lung volume adjusted for sex, age, height, pack-years of smoking, CT scanner brand/make, and lobar volume, lobar emphysema was directly related to subsegmental WA% in all bronchial paths but RB4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Using data from the COPDGene Study, we observed that emphysema mitigates the increasing effect of WA% on FEV 1 % predicted in subsegmental compared with segmental airways. CT scan measures of emphysema and lung volume adjusted for sex, age, height, pack-years of smoking, CT scanner brand/make, and lobar volume, lobar emphysema was directly related to subsegmental WA% in all bronchial paths but RB4.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It has since become the standard in quantitative CT image analyses to study the most peripheral airways. [12][13][14] African American smokers aged 45 to 80 years. Subjects with active lung disease other than asthma, emphysema, and COPD were excluded.…”
mentioning
confidence: 99%
“…The important role of small airway lesions has been well recognized in the airflow limitations in COPD [43]. Recently, it was reported that bronchodilation at the distal rather than the proximal airways determines functional improvement in airflow limitation in response to Tio in COPD [44]. If we had measured more peripheral sites of the airway dimensions through the development of CT technology, we may have provided some intriguing insights into the bronchodilator effect of Tio plus SFC.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Furthermore, CT scanning is a recognized technique to assess the presence, extent, and location (ie, lobar level) of emphysema. 7 CT scan can be used to classify subjects with COPD into emphysemapredominant (EP) or airway-predominant (AP) subtypes.…”
Section: Ct Scan Examinationmentioning
confidence: 99%